Sie sind auf Seite 1von 39

 F 0 F g K 1 K n
 K w g ν

x e

x a

z

z

=

0

F = m · a

M = J d dt

u R = R · i R

u L = L d dt i L

i C = C d dt u C

α

n+1

(n)·

x

a

(t) + ··· + α 3 x¨ a (t) + α 2 x˙ a (t) + α 1 x a (t) + α 0

= β 1 x e (t) + β 2 x˙ e (t) + ··· + β m+1

(m)·

x e

(t)

x e x a

x e x a

α 0 = 0

a

n+1

(n)·

x

a

(t) + ··· + a 3 x¨ a (t) + a 2 x˙ a (t) + a 1 x a (t)

= b 1 x e (t) + b 2 x˙ e (t) + ··· + b m+1

(m)·

x e

(t)

b 1 = 1 b 1 = 0

F 0

x e x w = 0 z = 0

F 0 =

x

x e

= F R F S

F g

F g F gz

Z g (p)
Z gz (p)
F g (p) = x
=
F gz (p) = x
=
w
N g
(p)
z
N g (p)
x · N g (p) = w · Z g (p)

d p 3 + c p 2 + b p + a) · x =

a, b, c x x w w p

α, β, γ

d

dt

d + c x¨ + b x˙ + a x =

x

 δ p 3 + γ p 2 + β p + α) · w δ w + γ w¨ + β w˙ + α w

w

= 0

w = 0

w t = 0

t 0

w = = w S

x s = α

a w S

w˙ = 0

w¨ = 0

.

.

.

d λ 3 + c λ 2 + b λ + a = 0

λ 1 λ 2

λ n

x h = D 1 e λ 1 t + D 2 e λ 2 t + ··· + D n e λ n t

N g F g (p) F gz (p)

F 0 (p) =

K

1 + p T aN s N + p 2 T A T aN s N

1

p T aN

p = 0

 ∆κ = κ(∞) − κ(0) κ(∞) = κ| ω→∞ κ(0) = κ| ω→0

κ(0) = π

2 arctan

K·s N

1 Re[F 0 ()] ω0

Im[F 0 ()] ω0

→∞

K

K = 144 κ() = π κ = 3 π

= 48 κ() = π κ = π

2

2

= π

2

F g (p)

t = t 0 t < t 0 t = t 0

x a = x a (t) t > t 0 t > t 0 x e 0 z ν 0

t = t 0 t > t 0 x e 0 z ν 0 t > t 0

x 1 x 2

x n

x 1 x 2 K K 1

x n K n n + 1

x 1 = x

x 2 = x˙

x 3 = x¨

x n =

(n1)·

x

y = K(w C 1 x C 2 x˙ C 3 x¨ − ··· − C n

(n1)·

x

b 1 = 1 b 2 b 3

b n+1 = 0

y = a 1 x + a 2 x˙ + a 3 x¨ + ··· + a n+1

(n)·

x

 )

a n+1

(n)·

x +···+a 3 x¨+a 2 x˙ +a 1 x = K W K C 1 xK C 2 x˙ K C 3 x¨−···− K C n

(n1)·

x

(n)·

x

a n+1

K

+ (n1)·

x

C n + a n

K

+

+

x¨ C 3 +

x˙ C 2 +

a

3

K

a

2

K

+ x C 1 + a K = w

1

=

(w

= 0)

+

(w = 0)

w t = 0 0 w S

t > +0

w = w S =

w,˙
w,¨
.
.
.
= 0
w S
⇒ x s =
C 1 + a 1
K

λ n a n+1

K

+ λ n1 C n + a n

K

+

λ 2 C 3 + a K

3

+ λ C 2 + a

K

2

+ 1 C 1 + a K = 0

1

x h = D 1 e λ 1 t + D 2 e λ 2 t + ··· + D n e λ n t

D 1

x = x s + x h =

w S

C 1 + a 1
K

+ D 1 e λ 1 t + D 2 e λ 2 t + ··· + D n e λ n t

D n

λ 1

λ n

K w =

x s
(4)
1
=
w s
C 1 + a 1
K

K w = 1

K C 1

C n

λ n K w

K

a

n+1

=q n T n

+λ n1 K w C n + a n

K

=q n1 T n1

+··· + λ 2 K w C 3 + a K

3

=q 2 T 2

+λ K w C 2 + a K

2

=T

x

w = K w

1

1 + p T + q 2 p 2 T 2 + ··· + q n p n T n

+1 = 0

K w C 1 K C 1 q 2

q n T K C 2 C n

λ 1

λ n

K 1 K n

x

w = K w

1

1 + p T + q 2 p 2 T 2 + ··· + q n p n T n

x

y

K w , T, q 2 , q 3 ,

, q n K, K 1 , K 2 ,

w x = K w

, K n

T = 0 q ν K =

 K 1 , K 2 , , K n K

K w

q 2 , q 3 ,

T

, q n

K w

K w = 1

x

w = K w

1

1 + p T + q 2 p 2 T 2 + ··· + q n p n T n

q 2

q n

x

w = K w

1

1 + p T + q 2 p 2 T 2 + ··· + q n p n T n